Motivational Attributes and Factors Affecting Spending of Cruisers in the Greek Islands - PAPADOPOULOU, Georgia (Journal of Environmental Management and Tourism, 2020)
This paper focuses on the motivational attributes of Europeans and North Americans experiencing a cruise trip to Greece and the factors affecting spending at the transit ports and on the cruise ship. Tourists from Europe and North America are motivated to cruise in Greece for various reasons. Some of the motivational factors that influence cruise touring destinations included pricing, self-fulfillment, shopping, security, culture, and the availability of social and economic amenities. The tourism industry is one of the critical sectors that directly impact the international economy, not counting the economy of the preferred destinations. Other attributes that motivate the European and North American cruising tourists to experience a cruising trip in Greece included fair pricing of the commodities, availability of social, recreational, and economic amenities that improves the quality of life of the travelers. Local authorities are encouraged to invest more in projects that support cruising in Greece and security to ensure that the foreign tourists are more motivated to cruise in Greece.